Mid-upper arm circumference in pregnant women and birth weight in newborns as substitute for skinfold thickness: findings from the MAASTHI cohort study, India - Giridhara R. Babu; Aritra Das; Eunice Lobo; Deepa R; Daisy A. John; Prashanth Thankachan; Sonalini Khetrapal; Sara E. Benjamin-Neelon; GVS Murthy (BMC, 2021)
Abstract Background Estimating total body fat in public hospitals using gold-standard measurements such as air displacement plethysmography (ADP), deuterium oxide dilution, or dual-energy X-ray absorptiometry (DXA) is unaffordable, and it is challenging to use skinfold thickness. We aimed to identify the appropriate substitute marker for skinfold thickness to estimate total body fat in pregnant women and infants. Methods The study is part of a prospective cohort study titled MAASTHI in Bengaluru, from 2016 to 19. Anthropometric measurements such as body weight, head circumference, mid-upper arm circumference (MUAC), and skinfold thickness were measured in pregnant women between 14 and 36 weeks of gestational age; while measurements such as birth weight, head, chest, waist, hip, mid-upper arm circumference, and skinfold thickness were recorded for newborns. We calculated Kappa statistics to assess agreement between these anthropometric markers with skinfold thickness. Results We found the highest amount of agreement between total skinfold thickness and MUAC (Kappa statistic, 0.42; 95 % CI 0.38-0.46) in pregnant women. For newborns, the highest agreement with total skinfold thickness was with birth weight (0.57; 95 % CI 0.52-0.60). Our results indicate that MUAC higher than 29.2 cm can serve as a suitable alternative to total skinfolds-based assessments for obesity screening in pregnancy in public facilities. Similarly, a birth weight cut-off of 3.45 kg can be considered for classifying obesity among newborns. Conclusion Mid-upper arm circumference and birth weight can be used as markers of skinfold thickness, reflecting total body fat in pregnant women and the infant, respectively. These two anthropometric measurements could substitute for skinfold thickness in low- and middle-income urban India settings.